Analysis of the cytotoxic, genotoxic and mutagenic potential of the hydroalcoholic extract of Morus nigra L. Leaves through the bioassay Allium cepa (Research, Society and Development, 2020)
Consumption of products and substances of plant origin is common practice in populations all over the planet. Morus nigra L. (blackberry) is a medicinal plant widely used in folk medicine, and has several active ingredients with therapeutic action, such as antioxidant, antinoceptive, hypoglycemic and anti-inflammatory activity. The aim of the present study was to analyze the possible cytotoxic, genotoxic and mutagenic activities of Morus nigra L. leaves through the Allium cepa test. For preparation of the extract were used blackberry leaves, collected in the city of Agricolândia-PI. Three different concentrations (0.007 mg / mL, 0.07 mg / mL and 0.7 mg / mL) were used, in addition to the negative and positive controls. For each extract concentration, 10 onion bulbs were used, which were exposed for germination. After growth, the roots were measured with the help of a ruler, cut and followed by the slide preparation procedure, which were visualized under a light microscope at 100x magnification and analyzed qualitatively for the presence of genetic damage. Statistical analysis was performed using the ANOVA system of mean sample results. After data analysis, it was observed that the size of root meristems indicated no toxicity, the mitotic indexes of A. cepa cells exposed at these concentrations were not statistically different from the negative control. The chromosomal aberrations found were not significant (P